Scrub typhus: A case report from Bangladesh - Shaila Rahman; Tamanna Bahar (Wolters Kluwer Medknow Publications, 2021)
Scrub typhus is an acute febrile illness caused by a Gram-negative obligate intracellular bacterium named Orientia tsutsugamushi. Although this zoonotic disease is common in tropical and subtropical regions, it is often underreported in Bangladesh. We present a case of scrub typhus in a 15-years-old male who presented with fever, eschar, hepatitis, and positive serology and got complete recovery with doxycycline.